Determinación de una plantilla tipo de requerimientos que se ajuste a las necesidades de las micro y pequeñas empresas para migrar a Cloud computing - Churo Hidalgo, William Gonzalo (2017)
This article presents a proposal to micro and small companies in Ecuador, to migrate their current hardware and software platforms to IT solution, focused on the hiring of cloud computing services. For this field research was conducted, in which two fundamental aspects are analysed: 1) Determine the current situation in relation to the IT requirements of this type of business and from these determine a template of type requirements and 2) Determine the offer of services in the market for these requirements, including costs of services per month and per user. To determine the current requirements, a survey was designed consisting of 14 questions that focus on determining the IT infrastructure, personnel, business applications required for the business and the monthly operating costs to operate its infrastructure. The results of this survey provide a set of baseline indicators that were established according to the number of times companies determine the need for the requirement. The next step was to analyse the providers of this type of services in the cloud, in order to determine the best performance they offer depending on the service characteristics and their costs. Depending on the type of requirements and the costs offered by the recommended suppliers, a basic proposal for the hiring of these services is determined.